ANALISA TINGKAT RISIKO BENCANA GEMPA BUMI DI WILAYAH BALI - Darsono, Rudy; Sukarasa, I Ketut; Agus Setiawan, Yohanes (BULETIN FISIKA, 2016)
Bali region is prone to earthquake disasters because it lies between the two zones that cause earthquake (back arc trust at the north and subduction zones at the south) and also vulnerable to earthquake disasters because of high population density . These conditions threaten the safety of lives and property of the population, so it needs to be research to analyze the risk of earthquake disaster in Bali. For identification of earthquake disaster risk, in this study using 3 factor: earthquake danger factor is Peak Ground Acceleration in Bali, vulnerability factor is population density every district in Bali, and resilience factors is HDI (Human Development Index) every district in Bali. PGA value calculation using the atenuation function of Fukushima and Tanaka, for disaster risk index calculation using AHP (Analytical Hierarchy Process). The conclusion, regions that obtained the highest level of earthquake disaster risk are Karangasem and northern Buleleng, while the lowest are southern part of Badung,  northern part of Gianyar and Nusa Penida.